How are social identities linked to self-conception and intergroup orientation? The moderating effect of implicit theories - HONG, Ying-Yi (Institutional Knowledge at Singapore Management University, 2003)
Social identity approaches assume that social identification affects both self-conception and intergroup orientation. The authors contend that such social identification effects are accentuated when people hold a fixed view of human character and attribute immutable dispositions to social groups. To these individuals, social identities are immutable, concrete entities capable of guiding self-conception and intergroup orientation. Social identification effects are attenuated when people hold a malleable view of human character and thus do not view social identities as fixed, concrete entities. The authors tested and found support for this contention in three studies that were conducted in the context of the Hong Kong 1997 political transition, and discussed the findings in terms of their implications for self-conceptions and the meaning of social identification.